Artificial insemination and laying cycle influence adaptive immune cell numbers and localization in the reproductive tract of turkey breeder hens - Yifan Chen; Sunantha Kosonsiriluk; Lillian X. Ehresmann; Kent M. Reed; Sally L. Noll; Ben W. Wileman; Marissa M. Studniski; Kahina S. Boukherroub (Poultry Science)
Weekly artificial insemination (AI) is a common practice on commercial turkey breeder farms. The aim of this study was to determine changes in stress as well as oviduct and systemic immunity in response to weekly artificial inseminations through the laying cycle of turkey hens. Hens were divided into sham (extender only) and semen (extender + sperm) treatments. Blood, uterovaginal junction (UVJ), vagina, and spleen were collected at start of lay, peak lay, and end of lay (n = 8-12 /group for blood and 5 for tissues). The heterophil to lymphocyte ratio (H:L) was significantly higher in the semen-inseminated hens compared with the sham-inseminated hens at peak lay (n = 0.05). Immunohistochemistry revealed a higher number of CD3+ T cells in sperm storage tubules (SSTs) and UVJ submucosa at the end of lay compared with start and peak of lay across insemination treatments (n = 0.07 and 0.01, respectively). Within the end-of-lay group, semen-inseminated hens showed a higher number of CD3+ T cells in SSTs and UVJ submucosa (n = 0.04 and 0.1, respectively). The number of IgM+ B cells was significantly higher at start of lay compared with end of lay in SSTs and spleen (n = 0.01 and 0.0001, respectively) regardless of insemination treatment. In the vaginal submucosa, the number of IgM+ B cells was significantly higher in the semen group compared with the sham group at peak lay (n = 0.04). The number of IgA+ and IgY+ B cells were higher in the UVJ submucosa at the end of lay compared with start of lay, regardless of insemination treatment (n = 0.0001 and 0.03 respectively). In summary, the localization and number of adaptive immune cells change in response to the presence of sperm and laying cycle and depend on factors including immune cell type and tissue compartment. This suggests that the adaptive immune system of the oviduct plays an important role in responding to sperm based on the stage of the laying cycle. Modulating this immune response could improve reproductive performance.